1987
DOI: 10.1111/j.1574-6968.1987.tb02111.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the plasmid pPGH1 in the phenol degradation ofPseudomonas putidastrain H

Abstract: Pseudomonas putida strain H (wildtype) was shown to harbour two plasmids with a molecular mass of about 50 kb and 200–220 kb, respectively. Evidence is presented that the larger one, pPGH1, is involved in the phenol degradation via the meta‐cleavage pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The Pseudomonas broad spectrum resistance plasmids confer additional resistance to phenylmercuric acetate (PMA), thimerosal, and methylmercury [1]. Pseudomonas putida strain H harbours the plasmids pPGH1 and pPGH2; the former is involved in phenol degradation via the meta-cleavage pathway [4]. Preliminary experiments revealed that strain H cells are resistant to 30/~g/ml HgCI 2.…”
Section: Introductionmentioning
confidence: 99%
“…The Pseudomonas broad spectrum resistance plasmids confer additional resistance to phenylmercuric acetate (PMA), thimerosal, and methylmercury [1]. Pseudomonas putida strain H harbours the plasmids pPGH1 and pPGH2; the former is involved in phenol degradation via the meta-cleavage pathway [4]. Preliminary experiments revealed that strain H cells are resistant to 30/~g/ml HgCI 2.…”
Section: Introductionmentioning
confidence: 99%